Subcapsular Liver Hematoma in HELLP Syndrome: Case Report - Kapan, Murat (Gastroenterology Res, 2010)
Subcapsular liver hematoma, as a rare complication of HELLP syndrome, must be managed in a tertiary center for prompt recognition and treatment with close monitoring of hemodynamic and coagulation parameters, treatment of underlying disorders, and assessment by the imaging techniques. These patients underwent different therapeutic options varying from conservative therapy to operative management, including liver transplantation. As a choice of treatment, patients with HELLP syndrome can be followed up conservatively in stable hemodynamic conditions. In this report, we presented a 32-year-old woman with subcapsular liver hematoma secondary to HELLP syndrome managed conservatively.